Effect of Root Pruning of the Growth of Transplanted Silver Fir Seedlings - Singh, R. V.; Sharma, K. C. (Indian Forester, 1985)
The results of an investigation conducted to study the effect of root pruning on the survival and growth of transplanted silver fir seedlings showed that root pruning improved root:shoot ration, but did effect significantly neither the survival nor the growth of the seedlings; pruning of 75% of the tap root, however, depressed growth of the seedlings slightly.